Etos Kerja “Semut” sebagai Simbol Maskot Indomaret - Rudi Prasetiyo; Rakhmat Saiful Ramadhani; Fatihatul Lailiyah (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
This study analyzes the mascot "Si Domar" used by Indomaret company as a brand icon through a semiotic approach. The purpose of this research is to reveal the meaning contained in Si Domar as a company icon. This study uses a qualitative descriptive research method. This mascot not only serves as an eye-catching visual element, but also as a communication tool that reflects the company's identity and values to consumers. Charles Sanders Peirce's semiotic analysis was used to decipher the signs contained in the visual representation of Si Domar, including visual aspects such as color, shape, and expression, as well as the messages conveyed through these symbols.The results of the study show that Si Domar plays an important role in building a positive image of Indomaret in the eyes of the public. This mascot successfully blends elements of local culture and modernization, creating a divisible symbol. The conclusion of this study confirms that a deep understanding of semiotics is essential in the development of effective visual communication strategies to strengthen brand identity. Thus, Si Domar is not only a visual icon, but also a representation of Indomaret's deep values and identity.